(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Cultural and postcolonial critic Homi Bhabha is credited with making “hybridity” a buzzword in literature and other cultural discourses for referring to the consolidation of assorted, often contrasting elements into a congruous whole. The alterations in the contributing factors, that defy the initial polarity, and are resultant of atypical aggregation, bring forth innovation, abundance and diversification, whether such a conflux take place in art language, literature or culture. On account of its novelty and cross-cultural interdependence, the notion of hybridity constitutes major characteristics of postcolonial theory and practice. Bhabha is the key architect of the term “Third Space” as well which refers to the crevice that develops between clashing cultures and which gives rise to new cultural identities. This in-between space captures the consequences of alienation, cosmopolitanism, diaspora, displacement, hybridity and transnationalism. Migrants, who are exposed to different cultures commonly, foster a third space or hybrid sensibility. The Satanic Verses by Salman Rushdie celebrates the ideas like hybridity and third space. For example, when Saladin and Gibreel fall from the aeroplane (a metaphor for third space, the in-between arena), their personalities begin to transform because along with them the exploding plane casts out “broken memories, lost loves and mother tongues”. The Satanic Verses is an exposition of the adequacy with which hybridity sums up the complexities of identity in the globalized existence. It accentuates the concurrence of cultures and advocates for the ascendancy of mongrelisation. The novel disarrays the dominance of certitude by recommending that it is detrimental to dislodge hybridity due to the delusion of purity. This paper is an attempt to display how The Satanic Verses resists the chimera of credibility and antagonizes any supplication for homogeneity.